2021
DOI: 10.1001/jamanetworkopen.2020.34208
|View full text |Cite
|
Sign up to set email alerts
|

Association of Firearm Access, Use, and Victimization During Adolescence With Firearm Perpetration During Adulthood in a 16-Year Longitudinal Study of Youth Involved in the Juvenile Justice System

Abstract: Key Points Question Are youths involved in the juvenile justice system who use, have access to, or have been injured by a firearm or threatened with a weapon during adolescence more likely to perpetrate firearm violence and own firearms in adulthood? Findings This cohort study of 1829 randomly selected youth newly detained in a temporary juvenile detention center found that 85% of males and 63% of females were involved with firearms as adolescents. Nearly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 101 publications
(154 reference statements)
0
32
0
Order By: Relevance
“…That general pattern appears to hold for victimization with firearms and perpetration of firearm violence (Beardslee et al, 2018; Goldstick et al, 2019a; Kalesan et al, 2019; Rowhani-Rahbar et al, 2015; Schmidt et al, 2019; Teplin et al, 2021; Turner et al, 2016; Wallace, 2017). One study found that twice the number of individuals who experienced threats with a weapon as an adolescent reported they perpetrated firearm violence in adulthood (43.8% vs. 20.6%) and almost half of those who had a gunshot injury in adolescence reported perpetrating firearm violence as an adult (48.4%) (Teplin et al, 2021). Other studies have found that victimization as an adolescent was associated with carrying a gun to school or work as an adult (Turner et al, 2016; Wallace, 2017) and carrying a gun is associated with increased substance use (Buschmann et al, 2017) as well as increased risk of firearm victimization and perpetration (Branas, Richmond, Culhane, Ten Have, & Wiebe, 2009; Oliphant et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…That general pattern appears to hold for victimization with firearms and perpetration of firearm violence (Beardslee et al, 2018; Goldstick et al, 2019a; Kalesan et al, 2019; Rowhani-Rahbar et al, 2015; Schmidt et al, 2019; Teplin et al, 2021; Turner et al, 2016; Wallace, 2017). One study found that twice the number of individuals who experienced threats with a weapon as an adolescent reported they perpetrated firearm violence in adulthood (43.8% vs. 20.6%) and almost half of those who had a gunshot injury in adolescence reported perpetrating firearm violence as an adult (48.4%) (Teplin et al, 2021). Other studies have found that victimization as an adolescent was associated with carrying a gun to school or work as an adult (Turner et al, 2016; Wallace, 2017) and carrying a gun is associated with increased substance use (Buschmann et al, 2017) as well as increased risk of firearm victimization and perpetration (Branas, Richmond, Culhane, Ten Have, & Wiebe, 2009; Oliphant et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Another study found that exposure to firearm violence in childhood is associated with increased distress (Mitchell et al, 2019). Other research suggests that access and exposure to firearms during adolescence increase risk of owning and carrying a firearm as well as experiencing and perpetrating firearm violence (Teplin et al, 2021). However, it is not clear whether or how cumulative negative life experiences such as adverse childhood experiences and adult victimization might increase firearm-related risks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce and prevent violence related injuries, particularly youth gun violence, researchers underscore the need to better understand antecedents of violence and the context within which violence occurs (Teplin et al, 2021). Prior research has established that both individual and community factors influence an individual's likelihood of experiencing and perpetrating violence, with adverse childhood experiences most robustly influencing violence (Leban & Gibson, 2020).…”
Section: Introductionmentioning
confidence: 99%